Direct blood analysis of Bartonella bacilliformis Multi Locus Sequence Typing in patients with Oroya’s fever during a Peruvian outbreak - Pons, Maria J. (2015)
ASTMH 64th Annual Meeting. October 25-29, 2015 Philadelphia Marriott Downtown Philadelphia, Pennsylvania USA